Thermal, chemical and chemothermal denaturation of yeast enolase. Issue 2 (2003) - Huang Huang, Ping Ping; Dong Dong, Aichun Aichun
Abstract : We studied the temperature‒ and denaturant‒induced denaturation of yeast enolase by means of Fourier transform infrared spectroscopy. The temperature‒induced denaturation/aggregation of the enzyme in the absence of denaturant was highly cooperative and occurred between 55 and 65 ° C with a midpoint of ~58 ° C. Above 55 ° C, the intensity at 1656 cm −1 (predominantly α‒helix) decreases as a function of temperature, accompanied by the appearance of two new bands at 1622 and 1696 cm −1, indicating the formation of intermolecular β‒sheet aggregates. Five clearly defined isosbestic points were observed, indicating a two‒state conformational transition. Addition of a non‒denaturing concentration of gdnHCl (0.4 M) caused the thermal denaturation/aggregation of the enzyme to proceed faster, but this revealed no unfolding intermediate. The gdnHCl‒induced unfolding was first detected at a gdnHCl concentration of above 0.4 M, evidenced by loss of α‒helix and β‒sheet structures as functions of denaturant concentration. The fully unfolded state was reached at a gdnHCl concentration of 1.6 M. A significant amount of intermolecular β‒sheet aggregate was detected at gdnHCl concentrations between 0.6 and 1.0 M, which disappeared as the denaturant concentration increased further. The gdnHCl‒unfolded state is a heterogeneous ensemble of turns, helix/loops, and random structures, which continues to change at higher concentrations of denaturant.